The Model of the Family and Family Upbringing Propagated By the Local Press of the Greater Poland Region in the Second Republic of Poland - Piwowarczyk, Mirosław (Pedagogika, 2013)
During the interwar period, local press played a major role in the socio-cultural life of the local communities in the Greater Poland region. With the high number of periodicals, the local press had a substantial influence on the socio - cultural life and education in the towns and cities of the region. It played a major educational role. It had an educational influence on the local communities, because the periodicals propagated models and forms of social and family life among them. The political and ideological stance of most of the periodicals was clearly defined as Catholic and national, therefore, the models of social activities that they promoted were consistent with this worldview. In consequence, the press propagated educational principles and ideas on upbringing, models of the family, a wife - mother, a husband - father, and children compatible with Catholic Social Teaching and the ideology of National Democratic political parties (Stronnictwo Narodowe [National Party], Narodowa Demokracja [National Democracy]). The model of the farmers’ families and those of the Middle Class was consistent with the clearly defined National Democratic ideology prevalent among the members of the local communities of Greater Poland, with its deep-rooted Catholicism, and with the experiences (characteristics, qualities) that became established in the times of the Partitions of Poland.